Pengaruh Jumlah Kunjungan Wisatawan, Tingkat Pendidikan Terhadap Penyerapan Tenaga Kerja dan Pertumbuhan Produk Domestik Regional Bruto di Provinsi Bali - I Komang Adyatama Candra Budhi; Putu Krisna Adwitya Sanjaya (Journal Of Business, Finance, and Economics (JBFE), 2024)
Gross Regional Domestic Product (GRDP) is one of the indicators to determine the economic growth of a region. The GRDP value will be an indicator of the region's ability to manage and utilize existing resources. In the Regency/City in Bali Province, there is still inequality in GRDP growth which indicates weaknesses in the management of existing resources. Based on this phenomenon, the objectives of this study are (1) To analyze the direct influence of the number of tourist visits and education levels on labor absorption in the Regency/City of Bali Province. (2) To analyze the influence of the number of tourist visits, education levels, and labor absorption on GRDP growth in the Regency/City of Bali Province. (3) To analyze the direct influence of the number of tourist visits and education levels on GRDP growth indirectly through labor absorption in the Regency/City of Bali Province. The data used in the study are secondary data with a total of 144 observations using panel data, while the analysis technique used is path analysis to analyze the direct and indirect influences of each variable. Based on the results of the study, it shows that (1) The number of tourist visits and education levels have a positive and significant effect on labor absorption in the Regency/City of Bali Province. (2) The number of tourist visits has a positive and significant effect on GRDP growth, the level of education has a negative and significant effect on GRDP growth, labor absorption has a negative but not significant effect on GRDP growth in the Regency/City of Bali Province. (3) Labor absorption does not mediate the influence of the number of tourist visits and education level on GRDP growth in the Regency/City of Bali Province.